2021
DOI: 10.1002/mus.27324
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 in patients with myasthenia gravis: Epidemiology and disease course

Abstract: Introduction/Aims Coronavirus disease 2019 (COVID‐19), a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection, has become a global pandemic. Patients with myasthenia gravis (MG), often treated with immunosuppressants, might be at higher risk of developing COVID‐19 and of demonstrating a severe disease course. We aimed to study prevalence and describe features of COVID‐19 in MG patients. Methods In May 2020, we conducted telephonic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 13 publications
4
44
2
Order By: Relevance
“…After examining the titles and abstracts of the remaining articles, 19 studies with 152 patients with confirmed MG diagnosis and COVID-19 were included in the qualitative systematic review ( Fig. 1 ) [3] , [6] , [8] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] . Of these studies, 10 were case series, 8 were case reports, and one was a cohort study, as shown in Supplementary Tables 1 and 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After examining the titles and abstracts of the remaining articles, 19 studies with 152 patients with confirmed MG diagnosis and COVID-19 were included in the qualitative systematic review ( Fig. 1 ) [3] , [6] , [8] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] . Of these studies, 10 were case series, 8 were case reports, and one was a cohort study, as shown in Supplementary Tables 1 and 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous long-term treatment particularly in higher dose was reported to be among the most important predictors of severe COVID-19 in MG patients [29] . However, some reports have suggested that suppression of the immune response may be protective against infection since immunosuppression can decrease the dramatic upregulation of inflammatory cytokines that can cause complications [56] , [57] , while others suggested that the risk of COVID-19 in MG patients does not appear to be higher than that of the general population, regardless of immunosuppressive therapies [28] . We found that in our study, patients treated with prednisone/corticosteroids before the diagnosis of COVID-19 or during COVID-19 had a high rate of mortality when used alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current evidence on the relationship between MG and COVID-19 is highly variable. Some studies suggested that COVID-19 has a limited effect on most of the patients with MG, since most of the patients in these studies do not experience exacerbations of MG, and immunosuppressive therapy is relatively safe (23)(24)(25). In contrast, other studies found a high proportion of patients with MG exacerbations requiring rescue therapy or mechanical ventilation (26,27).…”
Section: Coronavirus Disease 2019 (Covid-19mentioning
confidence: 99%
“…Viral and bacterial respiratory infections are common triggers for exacerbation in MG. COVID19 has also been described as a trigger for exacerbation [3,[7][8][9], although MG worsening appears to be uncommon in COVID, affecting only 10-15% of patients [4,5]. Comparing this number to seasonal in uenza, a recent study performed before the coronavirus pandemic has shown that an in uenza-like illness (de ned as fever of ≥38℃ accompanied by cough and/or sore throat) resulted in exacerbation in 40% of myasthenic patients [10].…”
Section: Discussionmentioning
confidence: 99%
“…Exacerbation of MG during COVID19 infection appears to be uncommon, ranging from 10-15% [4,5]. The scenario of myasthenia exacerbation due to COVID19 can be challenging, both due to diagnostic concerns (is respiratory insu ciency related to hypoventilation secondary to muscle weakness or hypoxia secondary to pulmonary involvement?)…”
Section: Introductionmentioning
confidence: 99%